IMMU-25. RADIO-IMMUNOTHERAPY USING THE IDO PATHWAY INHIBITOR INDOXIMOD FOR CHILDREN WITH NEWLY-DIAGNOSED DIPG. Issue 2 (22nd June 2018) - Johnson, Theodore S; Aguilera, Dolly; Al-Basheer, Ahmad; Castellino, Craig; Eaton, Bree R; Esiashvili, Natia; Foreman, Nicholas; Heger, Ian M; Kennedy, Eugene P; Link, Charles J; Martin, William; Ring, Eric; et al.
Abstract: BACKGROUND: Indoximod is an IDO pathway inhibitor with a differentiated mechanism of action directly targeting immune cells to reverse the immune suppression generated by tumors. An ongoing phase-1b/2a study (NCT02502708) using indoximod in combination with temozolomide and/or re-irradiation for children with relapsed/refractory pediatric brain tumors has established the recommended phase-2 dose (RP2D) of indoximod for this regimen and has shown this approach to be well-tolerated and feasible in these highly complex and fragile patients. Diffuse Intrinsic Pontine Glioma (DIPG) is an FDA-designated orphan disease, with no curative treatment options and dismal prognosis. The primary hypothesis is that addition of indoximod-based immunotherapy to standard-of-care radiation, followed by immuno-chemotherapy with indoximod plus temozolomide will improve objective response rates, 12-month event-free survival, and median overall survival. DESIGN/METHODS: Newly-diagnosed DIPG patients age 3 to 21 years are treated with indoximod (RP2D) in combination with conformal radiation therapy (54 Gy), followed by cyclic immune-chemotherapy using indoximod (RP2D=38.4 mg/kg/day divided BID throughout each cycle) combined with temozolomide (200 mg/m2/day, days 1-5 of each 28-day cycle). Up to 30 patients may be enrolled. RESULTS: The trial is ongoing. At this time, we have enrolled the first 6 newly-diagnosed DIPG patients. At the end of the indoximod plus radiation block, the first two patients had objective tumor response without any significant adverse events to date. Interim outcome and safety data for the first 8 months of accrual will be presented.